2020
DOI: 10.1002/acr.24333
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risk in Knee Osteoarthritis: A Systematic Review and Meta‐Analysis of Observational Studies

Abstract: Objective To assess the association between occupational exposures and knee osteoarthritis (OA). Methods We systematically searched for observational studies that examined the relationship between occupational exposures and knee OA and total knee replacement. Four databases were searched up to October 1, 2019. Two reviewers independently assessed study quality using the Newcastle‐Ottawa Scale and evidence quality using the Grading of Recommendations Assessment, Development and Evaluation approach. Subgroup met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 39 publications
(42 reference statements)
4
47
0
Order By: Relevance
“…Collectively, our observations provide support for our hypothesis that intermittent activity-related exposures are risk factors for flares. Mechanical exposures, including occupational physical loading 41 , 42 , often associated with incidence and progression, may also contribute to ‘acute-on-chronic’ flares. These exposures have been proposed to have an etiological role, and also represent potentially modifiable risk factors for the etiopathogenesis 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our observations provide support for our hypothesis that intermittent activity-related exposures are risk factors for flares. Mechanical exposures, including occupational physical loading 41 , 42 , often associated with incidence and progression, may also contribute to ‘acute-on-chronic’ flares. These exposures have been proposed to have an etiological role, and also represent potentially modifiable risk factors for the etiopathogenesis 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In the northern region of Portugal, industrial employment is higher than the national average, and agriculture, forestry, construction, and manufacturing industries are important sources of employment ( 53 ). A recent systematic review concludes that people in the agriculture, construction, and metal industries have a higher probability of developing knee OA ( 54 ). Additionally, due to current sociodemographic characteristics of this region and the projected prevalence of chronic diseases and long-term disability, the northern region of Portugal is expected have a higher proportion of individuals with at least one chronic disease and long-term disability in 2031, mainly due to lower education levels ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and prevalence of OA have risen rapidly in the past few years. The pathogenesis of OA is complex and not completely explained, but adverse lifestyles and health conditions, including excessive physical labor ( 4 ), drinking alcohol ( 5 ), smoking ( 6 ), Type 2 diabetes, and obesity ( 7 , 8 ), as well as an increase of sex hormone-binding globulin (SHBG), calcium, testosterone (T) and estradiol (E2) ( 9 ), and an overburden of pathologic factors such as inflammatory cytokines and matrix degradation are known to contribute ( 10 , 11 ). Additionally, previous epidemiological studies have reported an association between coffee consumption and OA risk ( 12 ).…”
Section: Introductionmentioning
confidence: 99%